2020
DOI: 10.1016/j.bbih.2020.100093
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cognitive function in Crohn’s disease: Relationship to disease activity

Abstract: Background & aims Impaired attention and response inhibition have been reported in patients with Crohn’s disease (CD) in clinical remission. Prospective studies are needed to determine whether this is a stable feature of CD and whether a similar impairment is evident in ulcerative colitis (UC). Thus, our aims were to examine whether patients with CD and UC exhibited a persistent impairment in attentional performance, and if this impairment was related to key biological indices of relevance to cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
2
14
1
1
Order By: Relevance
“…TBI and DSS-induced colitis are reported to alter social behavior in rodents [ 55 , 56 ]. We next assessed the effect of intestinal inflammation during chronic TBI on social behavior using Crawley’s three-chamber social approach task (SA) 3 weeks after the onset of intestinal inflammation (PTD51-54).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TBI and DSS-induced colitis are reported to alter social behavior in rodents [ 55 , 56 ]. We next assessed the effect of intestinal inflammation during chronic TBI on social behavior using Crawley’s three-chamber social approach task (SA) 3 weeks after the onset of intestinal inflammation (PTD51-54).…”
Section: Resultsmentioning
confidence: 99%
“…Deficits in social recognition and memory were reported in pediatric and young adult mice subjected to TBI [ 45 , 56 , 78 ]. Inflammatory bowel disease (IBD) is also associated with neurological dysfunction in patients [ 55 , 79 , 80 ] and is a risk factor for neurodegenerative diseases and neurodevelopmental disorders [ 81 – 84 ]. Rodent models of acute colitis report deficits in working, declarative, and social recognition and memory [ 19 , 22 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the colitis mouse model induced by dextran sodium sulfate, elevated frequencies of inflammatory M1-like microglia, and increased release of pro-inflammatory cytokines are observed in the hippocampus [ 38 ]. In clinical studies, patients with inflammatory bowel disease present with impaired cognitive function and decreased hippocampal activity, as assessed by magnetic resonance imaging [ 39 , 40 ]. In line with this evidence, we found that fiber deficiency impaired colonic homeostasis, including the loss of barrier integrity and inflammation, which is concomitant with the appearance of hippocampal neuroinflammation and synaptic impairment, indicating a perturbed gut-brain axis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increasing evidence supports the gut-brain axis, which involves complex interactions between the central nervous system and the enteric nervous system 135 . Patients with inflammatory bowel disease (such as Crohn’s disease) show altered brain structure and function 136 , impaired cognitive functions 137 , and a higher risk of depression and anxiety 138 . Multi-system analysis using biobank-scale data may provide insights for inter-organ pathophysiological mechanisms and prevention and early detection of brain diseases.…”
Section: Discussionmentioning
confidence: 99%